Effect of the Affordable Care Act on the Cost of Intrauterine Device Insertion [10N]. (May 2016) - McCarthy, H. Catherine; Howard, Brandon; Eid, Sherrine; Strachan, Gordon; Tang, Boxiong
Abstract : INTRODUCTION: The Affordable Care Act (ACA), signed into US law in 2010, required health plans to cover preventative medicine at 100%. This service was extended to include contraception in 2012/2013. An analysis was conducted to compare the combined cost of intrauterine devices (IUDs) and insertion before and after the ACA. METHODS: Truven Health MarketScan database is a large claims database containing data from patients enrolled in employer and commercial health plans, including a sampling of Medicaid supplemental plans. Truven's Treatment Pathways 3.0 tool was used to retrospectively examine the total cost, including patient out-of-pocket cost and insurance reimbursement, associated with IUDs and insertion for the years 2010 through 2014. The data were summarized descriptively. RESULTS: There was little change in the mean total cost for IUDs and insertion from 2010 to 2014 ($146.09 to $143.04, respectively; range: $137.43 to $146.09). On the other hand, mean patient out-of-pocket cost decreased substantially from $25.06 in 2012 to $5.88 in 2013 and $4.76 in 2014. A corresponding increase in mean insurance reimbursement from $112.36 in 2012 to $138.90 in 2013 and $138.27 in 2014 was noted. CONCLUSION: While the overall mean cost of IUD insertion remained generally stable, a dramatic decrease in the cost to the patient was noted in 2013 following the ACA, which was sustained through 2014. Whether the decrease in patient out-of-pocket cost associated with IUD insertion will have an effect on the rate of IUD use among women in the US remains to be determined. Support: Teva Pharmaceuticals.